The Use of Synthetic Data in Healthcare Research and AI Training: A New Paradigm for Privacy and Progress - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Meta Description: Explore the transformative role of synthetic data in healthcare research and AI training. Learn about the benefits for patient privacy and ...
Keywords: Digital Health; Healthcare Innovation; Medical AI; Clinical Decision Support; Medical Ethics